Postantibiotic effects and Burkholderia (Pseudomonas) pseudomallei: evaluation of current treatment. - Walsh, A L (1995)
The postantibiotic effects (PAEs) OF 16 antibiotics or antibiotic combinations currently used against Burkholderia (Pseudomonas) pseudomallei were determined. The beta-lactams had zero PAEs, while the carbapenems and ciprofloxacin induced median PAEs of 1 and 5 h, respectively. These results emphasize the need to maintain antibiotic levels above inhibitory concentrations in blood throughout the dosing interval in cases of severe melioidosis.